(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2013)
How are we to conceptualize the changes in contemporary cities on the basis of their ambiances? What about the sensory production of urban territories? What happens when our aim is no longer just to design space but also to install an atmosphere? This paper proposes a hypothesis: we are currently witnessing the ‘setting of ambiance’ in urban spaces. Several ambiance operating modes are identified in order to implement this argument.How are we to conceptualize the changes cities on the basis of their ambiances? What about the sensory production of urban territories? What happens when our aim is no longer just to design space but also to install an atmosphere? This paper proposes a hypothesis: we are currently witnessing the ‘setting of ambiance’ in urban spaces. Several ambiance operating modes are identifying in order to implement this argument.